Responsible consumption and its relationship with the circular economy: perspective from households - Quezada, Andrea (2024)
Consumerist behaviors, the culture of waste, and the linear economic model are factors that have caused the emergence of a climate crisis that threatens society and the environment. Its consequences have given rise to environmental awareness from an economic perspective, with a circular economic model that guides responsible behavior on the part of consumers, achieving sustainable alternatives. But what is the relationship between the behavior of responsible consumers and the concept proposed by the circular economy? To answer this question, it was proposed to evaluate the consumption characteristics in the homes of a significant sample of distance learning university students, from the perspective of the principles of the circular economy. Applying a mixed research method with quantitative and qualitative approaches, and a descriptive-correlational scope, the main results were that the relationship between circular economy and responsible consumption is moderately positive, verifying its alignment with the descriptive results, where, depending on the principles of the circular economy, students show moderate responsible behavior in their homes, allowing us to contribute towards a culture with sustainable consumption patterns.